Perception of Employer Branding in Social Media – Empirical Study and Implications - Brusiło, Agata (Employer branding w mediach społecznościowych – badania empiryczne i spostrzeżenia dla praktyki gospodarczej, 2025)
Aim: This study examined how often Wrocław university students checked an employer’s online presence before applying, how negative evaluations shaped their intentions, and which social-media activities they considered most attractive (April – June 2021). It responds to intensifying labour-market competition and the need for early, effective communication with potential employees. Methodology: A diagnostic survey of purposively selected Bachelor’s and Master’s students recruited via social platforms, complemented by a literature review on employer branding as both a theoretical concept and an empirical phenomenon. Results: Most respondents reviewed a company’s online activity prior to applying, and negative reviews strongly discouraged applications. The analysis identified the employer-branding activities perceived as most effective for young jobseekers; notably, humorous content attracted high interest, underscoring the value of informal communication in building employer–candidate relationships. Implications and recommendations: The findings can help organisations align employer-branding strategies with the expectations of students in Wrocław and increase recruitment efficiency. Investing early in internships and initiatives that support professional development is advised, along with attentive, transparent online communication. Originality/value: By focusing on individuals just entering the labour market, the paper offers a fresh perspective on effective employer branding amid demographic decline and provides practical insights for human resource management.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 3, s. 1-20